Peran Ibu dalam Menstimulasi dengan Perkembangan Anak di Posyandu - I Ketut Labir; Ni Luh Kompyang Sulisnadewi; I Nengah Sumirta (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2016)
The purpose of this study was to determine the relationship between the mother's role in stimulating the development of children in Pustu that Work Area Cemagi health center, district. Mengwi, Badung regency. This study used a quantitative method to approach cross-sectional study. About 110 was taken with total sampling technique. Data collected by questionnaires for 4 months and a variable relationship analysis performed with Spearman Rank Correlation test. The results showed the P value 0.000 less than value = 0:05 so that it can be concluded that there is a relationship between the mother's role in stimulating with the development of children The value coefficient correlation (r) is 0.741 which means to have a very strong correlation. Results of this study can be concluded there is a correlation betwen mother's role in stimulating with the evelopment of the children, and can be used as a handle or a reference by health workers in Pustu Cemagi for the detection of early childhood development.